Histone-Like Nucleoid Structuring Protein Modulates the Fitness of tet(X4)-Bearing IncX1 Plasmids in Gram-Negative Bacteria - Cai, Wenhui; Tang, Feifei; Jiang, Lijie; Li, Ruichao; Wang, Zhiqiang; Liu, Yuan (Frontiers in Microbiology, 2021)
The emergence of plasmid-mediated tigecycline resistance gene tet(X4) poses a challenging threat to the public health. Based on the analysis of tet(X4)-positive plasmids in NCBI database, we found that IncX1 type plasmid is one of the most common vectors for spreading tet(X4) genes, but the mechanisms by which these plasmids adapt to host bacteria and maintain the persistence of antibiotic resistance genes (ARGs) remain unclear. Herein, we investigated the underlying mechanisms of how host bacteria modulate the fitness cost of IncX1 plasmids carrying tet(X4) gene. Interestingly, we found the tet(X4)-bearing IncX1 plasmids encoding H-NS protein imposed low or no fitness cost in E. coli and K. pneumoniae, instead partially promoted the virulence and biofilm formation in host bacteria. Regression analysis revealed that the expression of hns gene in plasmids was positively linked with the relative fitness of host bacteria. Furthermore, when pCE2:hns was introduced, the fitness of tet(X4)-positive IncX1 plasmid pRF55-1 without hns gene was significantly improved, indicating that hns mediates the improvement of fitness. Finally, we showed that the expression of hns gene is negatively correlated with the expression of tet(X4) gene, suggesting that the regulatory effect of H-NS on adaptability may be attributed to its inhibitory effect on the expression of ARGs. Together, our findings suggest the important role of plasmid-encoded H-NS protein in modulating the fitness of tet(X4)-bearing IncX1 plasmids, which shed new insight into the dissemination of tet(X4) gene in a biological environment.